Memory as belonging: existential concretization in the work “The Truth About Me: a Hijra Life Story” by A. Revathi - SOUZA, Natália Galdino de (2024)
This work seeks to discuss the concepts of memory, resistance and belonging, through reflections on some authors such as Alfredo Bosi (1996), Augusto Sarmento-Pantoja (2022), Tânia Sarmento-Pantoja (2022) with regard to resistance; Maurice Halbwachs (1990), Michael Pollak (1992) on the concepts of memory; Sandra Regina Lestinge (2004) and Lucimara Valdambrini Moriconi (2014) on belonging, among others who corroborate the development of this work. The aim of this research is to understand relations of resistance as a way of existing and to understand the process of memory for existential realization. The corpus of this research is chapters 1, 2 and 3 of the autobiographical work “The Truth About Me: A Hijra Life Story by A. Revathi”. To develop this research, we used the method of qualitative bibliographical research based on a theoretical-critical analysis of the selected work. As a result, we witness through Revathi's narrative a resistance based on the need for survival, where we are introduced to her trajectory as a Hijra and how these memories were/are essential for existential fulfillment, in order to be who you have always been.